Edukasi Kesehatan: Cegah Diabetes Melitus Sejak Dini - Shafa, Salsabila; Rahayu, Hesti; Abida P.P, Nafisya Nur; Azzahra, Aulia; Alsyalumah, Bulan Aulia; Putri K, Jovita (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Diabetes mellitus is a non-communicable disease with a rising prevalence in the community. It can be prevented through increased knowledge, lifestyle changes, and family involvement in daily management. This community service activity was conducted as an educational outreach for 30 women in a religious study group at Jl. H. M. Nur RT05/RW02 No.60, Kelurahan Krukut, Kecamatan Limo, Depok. The goal was to enhance participants’ knowledge and awareness in preventing and recognizing early risks of diabetes, as well as managing the disease independently at home. The interactive education session included pre-test and post-test assessments. Results showed an increase in average scores from 70,67 to 87,67, indicating a 22-point or 33,5% improvement in understanding. Through this activity, participants are expected to adopt healthier lifestyles, identify early symptoms, and support family members in diabetes prevention and management at home.